The Essl Collection : the first view. - Essl, Karlheinz; Fuchs, Rudi H.; Tesar, Heinz; Sammlung Essl, Klosterneuburg (Köln : DuMont Buchverlag, 1999)
The book is published in conjunction with the opening of the new museum Sammlung Essl in Klosterneuburg (Wien) on November 5, 1999
Alechinsky, Pierre ; Anzinger, Siegfried ; Appel, Karel ; Attersee, Christian Ludwig ; Balkenhol, Stephan ; Baselitz, Georg ; Bohatsch, Erwin ; Brus, Günter ; Clemente, Francesco ; Damisch, Gunter ; Eisler, Georg ; Export, Valie ; Flanagan, Barry ; Fontana, Lucio ; Förg, Gunther ; Francis, Sam ; Frohner, Adolf ; Gilbert & George ; Gironcoli, Bruno ; Hartung, Hans ; Hollegha, Wolfgang ; Holzer, Jenny ; Hundertwasser ; Immendorff, Jörg ; Jorn, Asger ; Jungwirth, Martha ; Katz, Alex ; Kippenberger, Martin ; Kirkeby, Per ; Kocherscheidt, Kurt ; Kogler, Peter ; Kounellis, Jannis ; Lafontaine, Marie-Jo ; Lassnig, Maria ; Lüpertz, Markus ; Messensee, Jürgen ; Mikl, Josef ; Music, Zoran ; Nitsch, Hermann ; Oberhuber, Oswald ; Oehlen, Albert ; Paik, Nam June ; Paladino, Mimmo ; Penck, A.R. ; Pichler, Walter ; Polke, Sigmar ; Prachensky, Markus ; Quinn, Marc ; Rainer, Arnulf ; Richter, Gerhard ; Ringel M.J.M. ; Ringel, Franz ; Rockenschaub, Gerwald ; Roth, Dieter ; Salle, David ; Saura, Antonio ; Scheibl, Hubert ; Schmalix, Hubert ; Schnabel, Julian ; Scully, Sean ; Soulages, Pierre ; Staudacher, Hans ; Tàpies, Antoni ; Vedova, Emilio ; Weiler, Max ; West, Franz ; Wotruba, Fritz ; Zechner, Johanes ; Zitko, Otto ; Zobernig, Heimo
biog. p. 382-395, bibliog. p. 396-423
Engels
boek